Improvement Of Soil Engineering Characteristics Using Lime And Fly Ash - Athanasopoulou, Antonia; Kollaros, George (European Scientific Journal, ESJ, 2016)
A solution available to engineers for facing the problem of unsuitable soils for pavement foundation is the stabilization processes. Among then the use of chemical additives has gained popularity, particularly the last decade. The poor engineering characteristics of soils could be enhanced under the action of various agents and controlling factors, like the pozzolanic activity, the cation exchange and other already recognized reactions taking place in the soil-additive complex. In this research work the findings of laboratory tests for the stabilization of a problematic soil in Xanthi, Northern Greece area are presented. For the testing program a commercial lime and a fly ash from an Electric Power Station have been elected. Various percentages have been used for the preparation of soil-additive mixtures. Based on the findings of the present study, fly ash could be recommended as an effective agent for the improvement of swelling soils, having the benefit of reducing the negative impacts to the environment. The results highlight the need for further investigation of clay soil characteristics after their chemical stabilization with substances freely available or with a low cost, if the intention is to use such soils in highway construction works..